2022
DOI: 10.1007/s13201-022-01747-8
|View full text |Cite
|
Sign up to set email alerts
|

A multi-criteria approach to drinking and irrigation water assessment of spring water in Igbo-Etiti, Nigeria

Abstract: The study aimed at assessing the spring water within Igbo-Etiti, Nigeria, for drinking and irrigation applications using physicochemical parameters, water quality index, mineral and trace elements, pollution indices, and risk assessment. Standard methods were used to determine the physicochemical properties of the spring water in rainy and dry seasons. Trace metals such as Pb, Cd, Zn and Cu were determined with atomic absorption spectrophotometer. The results showed that most of the physicochemical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…The results of this study successfully showed that combining the multivariate statistical method, the simple variables traits analysis, and the computation of irrigation indices makes it possible to predict water quality trends. Thus, they support multiple index approaches to irrigation water quality assessment (Ezea et al, 2022). This study's results confirm Sangare et al's (2023) recent findings about using the Niger River water for irrigation.…”
Section: Chloroalkaline Indicessupporting
confidence: 86%
“…The results of this study successfully showed that combining the multivariate statistical method, the simple variables traits analysis, and the computation of irrigation indices makes it possible to predict water quality trends. Thus, they support multiple index approaches to irrigation water quality assessment (Ezea et al, 2022). This study's results confirm Sangare et al's (2023) recent findings about using the Niger River water for irrigation.…”
Section: Chloroalkaline Indicessupporting
confidence: 86%
“…In a bid to find out the suitability of water, the Doneen plot used the PI and classified irrigation water in three different classes: Class-I, Class-II, and Class-III. Only Class-I and -II types of water are suitable for irrigation [3,[55][56][57]. From the plot below, 100% of water samples from both the River Karawa and River Iyiaji fell under Class-I.…”
Section: Ion Chemistrymentioning
confidence: 99%